Architects' data / Ernst Neufert ...[et al] - Neufert, Ernst
"Originally Published in the German Language by Vieweg + Teubner, 65189 Wiesbaden, Germany, as "Ernst Neufert: Neufert Bauentwurfslehre. 41. Auflage (41st Edition)."